Education for peace: The politics of adopting and mainstreaming peace education programs in a post-conflict setting - Kuppens, Line (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
Education for peace: the politics of adopting and mainstreaming peace education programs in a post-conflict setting, by Vanessa Tinker, Bethesda, Academica Press, 2015, 262 pp., US 74.95 (hardcover), ISBN 978-1-68053-007-0.